A study to investigate the influence of cardiac motion on the robustness of pencil beam scanning proton plans in oesophageal cancer. (October 2020) - Thomas, Melissa; Defraene, Gilles; Levis, Mario; Sterpin, Edmond; Lambrecht, Maarten; Ricardi, Umberto; Haustermans, Karin
Abstract: While proton therapy offers an excellent dose conformity and sparing of organs at risk, this can be compromised by uncertainties, e.g. organ motion. This study aimed to investigate the influence of cardiac motion on the contoured oesophagus using electrocardiogram-triggered imaging and to assess the impact of this motion on the robustness of proton therapy plans in oesophageal cancer patients. Limited cardiac-induced motion of the oesophagus was observed with a negligible impact on the robustness of proton therapy plans. Therefore, our data suggest that cardiac motion may be safely ignored in the robust optimisation strategy for proton planning in oesophageal cancer.